Análise do manejo de resíduos sólidos em comunidade isolada: o caso da praia das Sete Fontes, Ubatuba-SP - Zeron, Théo Sisla [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
One of the problems arising from mass tourism is the excessive generation of solid waste and its inadequate management. This research had as general objective to investigate the solid waste management in the Sete Fontes beach, in the city of Ubatuba-SP. It is a community, with a tourist activity, which does not have a waste collection service by the public authority. The methodology contemplated several actions, among them, we highlight the technical visits for non-participant observation, photographic records and the application of semi-structured interviews to the owners of the kiosks, which are the main waste generators. The results of the survey indicated problems with on-site waste. Among the problems identified is the large generation, mainly of recyclable material; accumulation of waste in the open air; improper disposal of some waste; and absence of comprehensive selective collection by the municipality. On the other hand, good initiatives have been identified, such as the separation of recyclable materials for sale; alternative to organic waste, as for natural compost; and reuse of waste

Um dos problemas decorrentes do turismo de massa é a excessiva geração de resíduos sólidos e seu gerenciamento inadequado. Esta pesquisa teve como objetivo geral investigar o manejo de resíduos sólidos na praia das Sete Fontes, no município de Ubatuba-SP. Trata-se de uma comunidade, com atividade turística, que não possui serviço de coleta de resíduos pelo poder público. A metodologia contemplou várias ações, entre elas, destacamos as visitas técnicas para observação não participante, registros fotográficos e aplicação de entrevistas semiestruturadas aos proprietários dos quiosques, que são os principais geradores de resíduos. Os resultados da pesquisa indicaram problemas relativos aos resíduos no local. Entre os problemas identificados está a grande geração, principalmente de material reciclável; acúmulo de resíduos a céu aberto; descarte inadequado de alguns resíduos; e ausência de coleta seletiva abrangente pelo município. Por outro lado, boas iniciativas foram identificadas, como a separação de materiais recicláveis para venda; destinação alternativa aos resíduos orgânicos, como para a compostagem natural; e reutilização de resíduos
Keywords: Resíduos; Resíduos sólidos; Turismo; Coleta seletiva de lixo; Impacto ambiental; Reaproveitamento (Sobras, refugos, etc.); Ubatuba (SP)